2005
DOI: 10.1029/2004gl022043
|View full text |Cite
|
Sign up to set email alerts
|

Response of terrestrial ecosystems to recent Northern Hemispheric drought

Abstract: Satellite normalized difference vegetation index (NDVI) observations reveal large and geographically extensive decreases in vegetation activity in Eurasia and North America between 1999 and 2002. In 2001, 73% of central southwest Asia exhibited NDVI anomalies that were more than one standard deviation below 21‐year average conditions, and in 2002, fully 95% of North America exhibited below‐average NDVI. This episode of large‐scale vegetation browning coincided with a prolonged period of below‐normal precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 28 publications
4
68
0
Order By: Relevance
“…This pattern is similar to that for NDVI 8 (Lotsch et al 2005). Figure 3 displays changes in (a) P 6-8 , and (b) NDVI 8 , from 1998 (pre-drought year) to 1999 (drought year), and those (d and e) from 2002 (drought year) to 2003 (post-drought year).…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…This pattern is similar to that for NDVI 8 (Lotsch et al 2005). Figure 3 displays changes in (a) P 6-8 , and (b) NDVI 8 , from 1998 (pre-drought year) to 1999 (drought year), and those (d and e) from 2002 (drought year) to 2003 (post-drought year).…”
Section: Resultsmentioning
confidence: 48%
“…A steep drying trend has been observed in soil moisture index values over Northern Hemisphere land areas since the mid-1950s, especially across northern Africa, Canada, Alaska, and Eurasia, including Mongolia (Dai et al 2004;Nandintsetseg and Shinoda 2012). In particular, below-normal precipitation in the Northern Hemisphere during 1999-2002 appears to have extensively decreased vegetation activity over Eurasia and North America, as revealed by the satellite-estimated normalized difference vegetation index (NDVI) (Lotsch et al 2005). The present work focuses on the 4-year, below-normal precipitation period of [1999][2000][2001][2002].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that soil and land surface conditions were more vulnerable to dust outbreaks in the 2000s than in the 1990s. A drying trendevident in an analysis of the Palmer Drought Severity Index (PDSI) (Dai et al 2004;Dai 2010), reduced precipitation, greater potential evapotranspiration owing to increased air temperature, and reduced normalized difference vegetation index (NDVI) in the 2000s (Lotsch 2005;Kurosaki et al 2011)-supports the demonstrated reduction in threshold wind speed in Mongolia.…”
Section: Introductionmentioning
confidence: 92%
“…Many researches have investigated NDVI trends in different regions, showing that despite great spatial heterogeneity, NDVI generally increased in national and regional scale in China [19,28], North America [2], east Asia [29] and Euraisa [30]. However, the increasing trends in these areas have slowed down or reversed since mid-1990s, which could be attributed to slowed down temperature trends or more frequent and severe drought [29,31]. The change in NDVI trends were analyzed by comparing trends before and after certain change points.…”
Section: Introductionmentioning
confidence: 99%